(untitled) (Applied Biological Research, 2017)
Genetic differences between rice genotypes were analyzed to assess genetic association between grain yield and yield contributing traits as a basis for selection of high yielding rice genotypes. Forty-two rice genotypes were evaluated for 11 quantitative traits to decide selection criteria under sandy loam soil conditions at Northern Hill Zone of Chhattisgarh (India). Results revealed enough variability in genotypes. Genotypic coefficient of variation was highest in grains panicle-1 (22.02), followed by spikelet fertility (18.30), spikelets panicle-1 (17.11), yield (15.395 kg ha-1). High estimates for heritability was exhibited by spikelet fertility (99.84) followed by days to 50% flowering (98.39), days to maturity (95.75), plant height (79.08). The number of grains panicle-1 showed highest positive direct effect (4.88) on grain yield followed by plant height (0.476), spikelet fertility (0.29) and days to 50% flowering (0.21). The characters showing high heritability coupled with high genetic advance and significant correlation with yield contributing traits may be used as selection criteria for grain yield under sandy loam soil conditions.